Non-declarative Sentences. - Zuber, Ryszard (Pragmatics & beyond ;, 1983)
Non-declarative sentences such as interrogatives, imperatives and exclamations are analyzed together as a single class. The author gives a general characterization of all three types and shows that there are no other types of non-declarative sentences. Definitions are offered for the notions of declaration and presupposition. These definitions are applicable to all types of sentence, both declarative and non-declarative. A defining characteristic of non-declarative sentences is that only strongly intensional operators can apply to them to form complex sentences. It is shown that this property.